2015
DOI: 10.1111/jns.12118
|View full text |Cite
|
Sign up to set email alerts
|

Impairment measures versus inflammatory RODS in GBS and CIDP: a responsiveness comparison

Abstract: This study aimed to 'define responder' through the concept of minimum clinically important differences using the individually obtained standard errors (MCID-SE) and a heuristic 'external criterion' responsiveness method in patients with Guillain-Barré syndrome (GBS) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). One hundred and fourteen newly diagnosed or relapsing patients (GBS: 55, CIDP: 59) were serially examined (1-year follow-up). The inflammatory Rasch-built overall disability scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…22 I-RODS has been recently suggested as a primary outcome measure for clinical trials in CIDP patients. 6,23 Further research is needed to dem- responsiveness has been previously showed, 6,24…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…22 I-RODS has been recently suggested as a primary outcome measure for clinical trials in CIDP patients. 6,23 Further research is needed to dem- responsiveness has been previously showed, 6,24…”
Section: Resultsmentioning
confidence: 95%
“…I‐RODS has been recently suggested as a primary outcome measure for clinical trials in CIDP patients . Further research is needed to demonstrate a responsiveness of the Serbian I‐RODS in order to fulfill the criterion of a satisfying outcome measure for clinical trials .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the I-RODS is the only interval measure to assess general functionality in patients with GBS, CIDP and MGUSP and has fulfilled all modern Rasch-built scientific requirements [11,13,27]. Its superiority over generally applied often ordinal-based impairment and disability measures has recently been demonstrated, as well as showing some cross-cultural validity [13,28]. Through a consensus meeting with international experts in the field of inflammatory neuropathies and patients' representatives, it was concluded that the I-RODS and the vigorimeter are the most sensitive tools in these conditions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Non‐responders were defined as patients who showed deterioration or minimal or no improvement after 6 months of treatment. Improvement was defined as improvement by at least the minimal clinical important difference on the I‐RODS; and/or an increase of ≥8 kPa on grip strength …”
Section: Methodsmentioning
confidence: 99%
“…Improvement was defined as improvement by at least the minimal clinical important difference on the I-RODS; and/or an increase of ≥8 kPa on grip strength. 15 Relapse occurrence after treatment withdrawal in MT patients was defined as any deterioration that required restarting treatment, as judged by the treating physician. Non-responders and MT patients who relapsed after treatment withdrawal were defined as having active disease at follow-up.…”
Section: Disease Activity At Follow-upmentioning
confidence: 99%